Protocol for a scoping review of patient engagement in pharmacy practice research - JoAnne Mosel; Anna Maria Chudyk; Janet Gunderson; Jenna Villarba; Caroline Monnin; Dana Turcotte; Abdullah Al Maruf; Jenna Kedy; Tracy Slaney (BMJ Open)
Introduction Over the last 20 years, the pharmacist’s role in healthcare has evolved, moving towards patient-centred care, collaboration and medication therapy management. Patient engagement in research is similarly being recognised as a transformative approach to healthcare due to its positive impact on outcomes and research relevance. However, patient engagement in pharmacy practice research is nascent. Therefore, we present a protocol for a scoping review to map the current state of patient engagement in pharmacy practice research, identifying its extent, range, nature, barriers, facilitators, impacts and gaps.Methods and analysis This protocol was developed in collaboration with persons with lived experience (PWLE). The scoping review will be conducted using established methodological frameworks and guided by the Best Practice Guidance and Reporting Items for the Development of Scoping Review Protocols and the Guidance for Reporting Involvement of Patients and the Public (GRIPP2) checklists. A comprehensive search involving three large databases, Medline (Ovid; 1946–Present), Embase (Ovid; 1974–Present) and Scopus (Elsevier), grey literature sources, forward and backward reference checking and consultation will be completed to retrieve the relevant literature. We will include published and unpublished research related to pharmacy practice that adopts patient engagement in research approach. Full-text screening will occur to determine eligibility for inclusion. Data will then be charted using a comprehensive extraction form. Qualitative data will be synthesised using basic qualitative content analysis, and quantitative data will be analysed using descriptive statistics. Regular meetings with PWLE and the research team will guide data analysis, interpretation and dissemination.Ethics and dissemination Ethics approval was not required for this protocol as we did not collect participant data. Findings may be disseminated through peer-reviewed publications, conference presentations, social media and knowledge user meetings, as informed by the perspectives of PWLE. Knowledge gained from this review will inform the development of strategies that support patient engagement, advance pharmacy practice research and have the potential to improve health outcomes and patient experiences.